2020
DOI: 10.1016/j.apsoil.2020.103681
|View full text |Cite
|
Sign up to set email alerts
|

Effect of monospecific and mixed litters on bacterial communities' structure and functions under contrasting Mediterranean climate conditions

Abstract: Global climate change is expected to contribute to intense droughts and heatwaves in the Mediterranean basin, motivating ecological research to explore the responses of litter microbial communities to more drastic climatic conditions. Here, we investigated how the functioning of microbial decomposition systems may be affected by litter source and mixing in two contrasting Mediterranean climate contexts: a sub-humid climate in France vs a semi-arid climate in Algeria. Studies included in situ incubation of litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 72 publications
(115 reference statements)
0
1
0
Order By: Relevance
“…In this study, we investigated two types of FFL differing in the initial litters used and climatic context. Indeed, it has been shown that mixing litters from different trees can potentially maximize the diversity of nutrient resources and consequently, favor microbial diversity [ 22 ], but this effect strongly varied according to the climate context [ 23 , 24 ]. Here, we hypothesized that the more chemically dissimilar the litters used, the higher the microbial diversity in the FFL.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we investigated two types of FFL differing in the initial litters used and climatic context. Indeed, it has been shown that mixing litters from different trees can potentially maximize the diversity of nutrient resources and consequently, favor microbial diversity [ 22 ], but this effect strongly varied according to the climate context [ 23 , 24 ]. Here, we hypothesized that the more chemically dissimilar the litters used, the higher the microbial diversity in the FFL.…”
Section: Introductionmentioning
confidence: 99%